Disseminated histoplasmosis - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Histoplasmosis is a worldwide fungal infectious disease caused by inhalation of spores of Histoplasma capsulatum. It may present as chronic pulmonary infection or in disseminated form. Disseminated histoplasmosis frequently affects the adrenal gland; however, unilateral involvement in immunosuppressed patients is the usual presentation. We report a case of an immunocompetent old male with history of weight loss, fever and bilateral adrenal masses. Computed tomography (CT)-guided biopsy of adrenal mass revealed histoplasmosis. This case report emphasizes the importance of considering fungal infection as differential diagnoses of mass lesions involving bilateral adrenals even if the patients are immunocompetent, along with the commoner lesions at these sites.